Pengaruh Utilitarian Value Dan Hedonik Value terhadap Kepuasan Pelanggan Toserba Ridho di Bintan - Betty Leindarita (Prosiding, 2020)
The purpose of this research was to determine: 1). Utilitarian value an affects on customer satisfaction, 2). Hedonic Value has an effect on customer satisfaction. 3) To find out whether utilitarian value and hedonic value affect on customer satisfaction. 4) To measure how much influence the utilitarian value and hedonic value have on customer satisfaction. This research is quantitative descriptive. The technique of collecting data using a questionnaire. The population in this study were the customers of Ridho Toserba in Bintan. The sampling method using the Slovin formula, then taken as many as 423 respondents. The results of this study were obtained: the results of the t test variable Utilitarian Value (X1) on customer satisfaction (Y) obtained t value of 5.905 which is greater than the t table (5.905 > 1.9719) with a significance of less than 0.05 ( 0.000 <0.05). In the hedonic variable value (X2) to customer satisfaction (Y), the value of t arithmetic 136,479 which is greater than t table (136,479 > 1.9719) with a significance of less than 0.05 (0.000 <0.05). The Multiple linear regression equation Y = (-1.351) + 0.413 (X1) + 0.674 (X2) + e. The conclusion of this study is it is known that the Utilitarian value and Hedonic Value variabels that influence customer satisfaction of Toserba Ridho in Bintan.